Multifunctional gradient structure artificial skin and preparation method and application thereof
By preparing a multifunctional gradient structure artificial skin, which combines a silicone layer, a biodegradable polymer/natural bioactive protein composite layer, and a hydrogel layer, the problems of poor mechanical strength and anti-infection performance of existing artificial skin are solved, and effective healing of chronic wounds is achieved.
Patent Information
- Application Number
- CN202511464296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2045-10-14
AI Technical Summary
Existing artificial skin products have poor mechanical strength and anti-infection properties, making it difficult to effectively promote the healing of chronic wounds.
A multifunctional gradient structure artificial skin is used, including a silicone layer, a biodegradable polymer/natural bioactive protein composite layer and a hydrogel layer. The intermediate layer is prepared by electrospinning technology to form a three-dimensional network structure. Combined with vacuum composite technology, skin with good mechanical properties and the ability to promote tissue regeneration is prepared.
It improves the skin's mechanical strength, prevents wound infection, promotes wound healing, and is suitable for the repair of chronic wounds.
Smart Images

Figure CN121154940A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of biomaterials and biomedical engineering technology, and particularly relates to a multifunctional gradient structure artificial skin as well as a preparation method and application thereof. BACKGROUND
[0002] Skin is the largest organ of the human body, providing a physical barrier for human tissues and protecting the body from the external environment. After the skin is damaged, it can complete self-repair through the hemostasis period, inflammation period, proliferation period and remodeling period. However, the repair process of chronic wounds such as skin surface burns, pressure ulcers, bedsores and diabetic foot is very difficult, and it is usually difficult to heal by itself, and needs to be treated with external means.
[0003] At present, there are many artificial skin products on the market and in research and development at home and abroad, which can effectively promote the healing of wounds and the regeneration of tissues. According to different functional properties, artificial skin is mainly divided into three categories of epidermal substitutes, dermal substitutes and full-thickness skin substitutes, which can play a targeted role in promoting the regeneration of epidermal / dermal tissues and promoting wound healing. Although the existing artificial skin products have achieved certain therapeutic effect in clinical application, there are still limitations such as low mechanical strength, poor anti-infection performance, and sensitization.
[0004] Therefore, it is necessary to provide an artificial skin with good mechanical strength, which can prevent wound infection and promote wound healing. SUMMARY
[0005] To solve the above technical problems, the present application provides a multifunctional gradient structure artificial skin as well as a preparation method and application thereof.
[0006] To achieve the above-mentioned purpose, the present application provides the following technical solutions:
[0007] The present application provides a multifunctional gradient structure artificial skin, which comprises an upper layer, a middle layer and a lower layer adhered to each other; the upper layer is a silica gel layer, the middle layer is a degradable polymer / natural bioactive protein composite layer, and the lower layer is a hydrogel layer; the raw materials for preparing the hydrogel layer include oxidized hyaluronic acid, carboxymethyl chitosan and collagen.
[0008] Technical principles: the upper layer of the present application is a silica gel layer, which is used to simulate the epidermis to keep the wound moist environment, and at the same time to play a barrier role; the intermediate layer is a degradable polymer / natural bioactive protein composite layer, which is used to enhance the mechanical properties; the lower layer is a hydrogel layer, which is formed by cross-linking hyaluronic acid and carboxymethyl chitosan to form Schiff base bond, and then cross-linking collagen through catalysis, the composition of the hydrogel layer is part of the extracellular matrix, and the three-dimensional network structure formed is conducive to the growth of cells, which can simulate the dermis to play the function of promoting tissue regeneration and remodeling, finally a kind of artificial skin with good mechanical strength, which can prevent wound infection and promote wound healing is obtained.
[0009] Further, the raw materials for preparing the silica gel layer include silica gel liquid A and silica gel liquid B; the components of the silica gel liquid A include silicon dioxide, vinyl silicone oil, methyl silicone oil and platinum gold water; the components of the silica gel liquid B include silicon dioxide, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil; the mass ratio of the silica gel liquid A and the silica gel liquid B is (0.5-2):1.
[0010] Further, the degradable polymer in the degradable polymer / natural bioactive protein composite layer is selected from polycaprolactone, and the natural bioactive protein is selected from type I collagen.
[0011] Further, the mass ratio of the degradable polymer and the natural bioactive protein in the degradable polymer / natural bioactive protein composite layer is (4-6):(6-4).
[0012] Further, the preparation method of the degradable polymer / natural bioactive protein composite layer includes: taking degradable polymer and natural bioactive protein as raw materials, and taking hexafluoroisopropanol as solvent, and the degradable polymer / natural bioactive protein composite layer is prepared by electrospinning.
[0013] Further, the process parameters of the electrospinning include: the flow rate of the spinning solution is 1-2mL / h, the working voltage is 13-15kV, the rotation speed of the aluminum foil receiver is 45-50r / min, the distance between the needle head of the syringe and the aluminum foil receiver is 15-17cm, and the needle head specification is 21G.
[0014] Further, the mass ratio of the oxidized hyaluronic acid, carboxymethyl chitosan and collagen is 20:30:(10-30).
[0015] Further, the raw materials for preparing the hydrogel layer also include glutamine transaminase; the mass ratio of the glutamine transaminase and the oxidized hyaluronic acid is 2.4:20.
[0016] The application provides a preparation method of the multifunctional gradient structure artificial skin, comprising the following steps: respectively preparing a silica gel layer, a degradable polymer / natural bioactive protein composite layer and a hydrogel layer; then combining the silica gel layer, the degradable polymer / natural bioactive protein composite layer and the hydrogel layer by vacuum compounding to obtain the multifunctional gradient structure artificial skin; and the vacuum compounding time is 24-72h.
[0017] The application further provides an application of the multifunctional gradient structure artificial skin in the preparation of a chronic wound repair material.
[0018] Compared with the prior art, the application has the following advantages and technical effects:
[0019] The carboxymethyl chitosan is obtained by methylation modification of chitosan, the chitooligosaccharide is a small molecular oligosaccharide with an amino side chain formed by degradation of shrimp and crab shells, has good biodegradability and biocompatibility, and the water solubility of chitosan is improved by methylation modification; the hyaluronic acid is a main component of the extracellular matrix of skin, has hydrophilicity and moisturizing property, and can promote wound healing; the collagen can greatly reduce the immune response and is beneficial to the adhesion and proliferation of fibroblasts; the hydrogel layer is prepared by using the above raw materials, which is beneficial to promoting wound healing.
[0020] The application adopts synthetic biodegradable polymers and natural bioactive proteins of biological sources to prepare the intermediate layer, the synthetic biodegradable polymers (such as polycaprolactone) are commonly used biomedical materials and can be used as in-vivo implant materials and drug controlled release materials; the natural bioactive collagen of biological sources has good biocompatibility and biodegradable safety, is a main component of most extracellular matrices, and has good immunogenicity.
[0021] The application adopts the degradable polymer as a raw material to prepare the intermediate layer, the obtained membrane has good mechanical properties, and the addition of a certain proportion of collagen significantly improves the mechanical properties of the membrane, and changes the characteristics of high toughness and low elasticity of the high polymer material. The hydrogel layer has the self-healing property, so that the hydrogel can be restored after breaking, improving the treatment effect of the hydrogel and improving the treatment effect; the carboxymethyl chitosan, the hyaluronic acid and the recombinant human collagen III in the hydrogel have good biocompatibility and biodegradability, and are beneficial to the repair of the diabetic foot wound surface. BRIEF DESCRIPTION OF DRAWINGS
[0022] The accompanying drawings, which form a part of the present application, are used to provide further understanding of the present application, and the schematic embodiments of the present application and their descriptions are used to explain the present application, and do not constitute improper limitations to the present application. In the drawings:
[0023] Figure 1 Micro-morphology (A), fiber diameter distribution (B), pore size distribution (D), fiber diameter statistical results (C) and pore size statistical results (E) of electrospun films prepared for Examples 1-3 and Comparative Example 1, wherein PCL is Comparative Example 1, P6C4 is Example 2, P5C5 is Example 1, P4C6 is Example 3 (same below);
[0024] Figure 2 Water contact angle of electrospun films prepared for Examples 1-3 and Comparative Example 1;
[0025] Figure 3 Mechanical properties of electrospun films prepared for Examples 1-2 and Comparative Example 1, wherein A is elastic modulus, B is elongation at break, C is tensile strength, D is ultimate load;
[0026] Figure 4 Mechanical properties of silica gel films and silica gel-electrospun films prepared for Example 2 step 2), wherein A is elastic modulus, B is elongation at break, C is tensile strength, D is ultimate load, Silica gel is silica gel film, Bilayer is silica gel-electrospun film;
[0027] Figure 5 Micro-morphology (A), pore size distribution (B) and pore size statistical results (C) of hydrogels prepared for Example 1, Examples 4-5 and Comparative Example 2, wherein R0 is Comparative Example 2, R1 is Example 4, R2 is Example 1, R3 is Example 5;
[0028] Figure 6 Cytotoxicity results of silica gel films prepared for Example 1 (A), electrospun films prepared for Examples 1-3 and Comparative Example 1 (B), and hydrogels prepared for Example 1, Examples 4-5 and Comparative Example 2 (C);
[0029] Figure 7 Effects of control group, hydrogels prepared for Comparative Example 2 and different concentrations of rhCol Ⅲ on cell migration and cell migration rate statistical results; wherein Control is control group, R0 is Comparative Example 2, 10 mg / mL, 20 mg / mL, 30 mg / mL are concentrations of rhCol Ⅲ, A is effects of control group and different concentrations of rhCol Ⅲ on cell migration, B is cell migration rate statistical results of control group and different concentrations of rhCol Ⅲ, C is effects of control group and hydrogels prepared for Comparative Example 2 on cell migration, D is cell migration rate statistical results of control group and hydrogels prepared for Comparative Example 2. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of the present application.
[0031] In order to make the above-mentioned objectives, characteristics and advantages of the present application more apparent, the present application will be further described in detail below with reference to the drawings and specific embodiments.
[0032] The multifunctional gradient structure artificial skin provided by the embodiments of the present application comprises an upper layer, a middle layer and a lower layer which are adhered to each other; the upper layer is a silica gel layer, the middle layer is a degradable high polymer / natural bioactive protein composite layer, and the lower layer is a hydrogel layer; the raw materials for preparing the hydrogel layer comprise oxidized hyaluronic acid, carboxymethyl chitosan and collagen.
[0033] In a preferred embodiment, the raw materials for preparing the silica gel layer comprise silica gel liquid A and silica gel liquid B; the components of the silica gel liquid A comprise silicon dioxide, vinyl silicone oil, methyl silicone oil and platinum gold water, and the mass ratio of the silicon dioxide, vinyl silicone oil, methyl silicone oil and platinum gold water is 0.35:0.47:0.178:0.002; the components of the silica gel liquid B comprise silicon dioxide, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil, and the mass ratio of the silicon dioxide, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil is 0.35:0.47:0.102:0.078; the mass ratio of the silica gel liquid A and the silica gel liquid B is (0.5-2):1.
[0034] In a preferred embodiment, the thickness of the silica gel layer is 0.3-0.5 mm. The silica gel layer in the present application serves as the upper layer and is used for simulating the epidermis to maintain a moist environment for the wound and simultaneously playing a barrier role.
[0035] In a preferred embodiment, the degradable high polymer in the degradable high polymer / natural bioactive protein composite layer is selected from polycaprolactone, and the natural bioactive protein is selected from type I collagen; the type I collagen is derived from bovine Achilles tendon. The degradable high polymer polycaprolactone is a commonly used biomedical material and can be used as an in-vivo implant material and a drug controlled-release material; the naturally derived bioactive collagen has good biocompatibility and biodegradable safety, is the main component of most extracellular matrices, and has good immunogenicity. The present application adds a certain proportion of collagen on the basis of the degradable high polymer, significantly improves the mechanical properties of the membrane, changes the characteristics of high toughness and low elasticity of the high polymer material, and enhances the mechanical properties of the multifunctional gradient structure artificial skin.
[0036] In a preferred embodiment, the mass ratio of the degradable polymer and the natural bioactive protein in the degradable polymer / natural bioactive protein composite layer is (4-6):(6-4).
[0037] In a preferred embodiment, the method for preparing the degradable polymer / natural bioactive protein composite layer comprises: using the degradable polymer and the natural bioactive protein as raw materials, using hexafluoroisopropanol as a solvent, and preparing the degradable polymer / natural bioactive protein composite layer by electrospinning. The degradable polymer / natural bioactive protein composite layer is prepared by electrospinning in the present application, and no toxic substances such as chemical cross-linking agents are used. The obtained product has the characteristics of non-toxicity and biocompatibility. The provided preparation method has the advantages of simple process, mild conditions, wide source of raw materials, and low cost, and is suitable for large-scale production and application.
[0038] In a preferred embodiment, the process parameters of the electrospinning include: the flow rate of the spinning solution is 1-2 mL / h, the working voltage is 13-15 kV, the rotation speed of the aluminum foil receiver is 45-50 r / min, the distance between the syringe needle and the aluminum foil receiver is 15-17 cm, and the needle size is 21G.
[0039] In a preferred embodiment, the concentration of the spinning solution used in the electrospinning is 15% (w / v).
[0040] In a preferred embodiment, the thickness of the degradable polymer / natural bioactive protein composite layer is 0.1-0.2 mm.
[0041] In a preferred embodiment, the mass ratio of the oxidized hyaluronic acid, the carboxymethyl chitosan, and the collagen is 20:30:(10-30), and is further preferably 20:30:20. The hydrogel layer in the present application is formed by cross-linking the oxidized hyaluronic acid and the carboxymethyl chitosan to form a Schiff base bond, and then cross-linking the collagen. The composition of the hydrogel layer is a component of the extracellular matrix, and the three-dimensional network structure formed is conducive to cell growth and can simulate the dermal layer to play a role in promoting tissue regeneration.
[0042] In a preferred embodiment, the collagen is selected from human recombinant type III collagen. The human recombinant type III collagen is obtained by genetic engineering technology, has a high degree of consistency with the amino acid sequence of human natural collagen, and has the characteristic structure of type III collagen. Therefore, the human recombinant type III collagen has low immunogenicity, can greatly reduce the immune response, and is conducive to the adhesion and proliferation of fibroblasts.
[0043] In the preferred embodiment, the preparation method of the oxidized hyaluronic acid comprises: oxidizing hyaluronic acid with sodium periodate as an oxidant to obtain the oxidized hyaluronic acid; the ratio of the amount of sodium periodate to the amount of hyaluronic acid is 2.5 mmol: 1 g; water is used as a solvent in the preparation of the oxidized hyaluronic acid; the oxidation is specifically carried out by stirring at room temperature in the dark for 2-6 h; and ethylene glycol is used to quench the oxidation after the oxidation is completed. The oxidized hyaluronic acid after aldehyde modification by sodium periodate can be crosslinked with carboxymethyl chitosan to form a Schiff base bond.
[0044] In the preferred embodiment, the raw material for preparing the hydrogel layer further comprises glutamine transaminase; the mass ratio of the glutamine transaminase to the oxidized hyaluronic acid is 2.4:20. The glutamine transaminase in the application is used to catalyze the crosslinking of collagen, thereby forming a hydrogel with a three-dimensional network structure.
[0045] In the preferred embodiment, the thickness of the hydrogel layer is 1-5 mm.
[0046] The application provides a preparation method of the multifunctional gradient structure artificial skin, which comprises the following steps: preparing a silica gel layer, a degradable high polymer / natural bioactive protein composite layer and a hydrogel layer respectively; and then combining the silica gel layer, the degradable high polymer / natural bioactive protein composite layer and the hydrogel layer by vacuum compounding to obtain the multifunctional gradient structure artificial skin; and the time for vacuum compounding is 24-72 h.
[0047] In the preferred embodiment, the preparation method of the silica gel layer comprises: uniformly stirring silica gel liquid A and silica gel liquid B, and then solidifying to obtain the silica gel layer; the stirring time is 5-10 min; the solidification temperature is room temperature, and the solidification time is 4-6 h.
[0048] In the preferred embodiment, the preparation method of the degradable high polymer / natural bioactive protein composite layer comprises: dissolving degradable high polymer and natural bioactive protein in hexafluoroisopropanol, stirring to obtain a spinning liquid, and then electrospinning the obtained spinning liquid to obtain the degradable high polymer / natural bioactive protein composite layer.
[0049] In the preferred embodiment, the preparation method of the hydrogel layer comprises: uniformly mixing oxidized hyaluronic acid, carboxymethyl chitosan, collagen and glutamine transaminase in water to obtain the hydrogel layer; and further preferably: placing glutamine transaminase in water, then adding oxidized hyaluronic acid to obtain a mixed solution 1; placing carboxymethyl chitosan and collagen in water to obtain a mixed solution 2; and uniformly mixing the mixed solution 1 and the mixed solution 2 by oscillation to obtain the hydrogel layer.
[0050] In a preferred embodiment, the combined order of the silica gel layer, the degradable polymer / natural bioactive protein composite layer and the hydrogel layer can be sequentially combining the silica gel layer, the degradable polymer / natural bioactive protein composite layer and the hydrogel layer, or combining the silica gel layer and the degradable polymer / natural bioactive protein composite layer first, and then combining the hydrogel layer.
[0051] The application further provides application of the multifunctional gradient structure artificial skin in preparation of a chronic wound repair material.
[0052] The room temperature in the embodiment of the application refers to "25±2℃".
[0053] Unless otherwise specified, the raw materials in the embodiment of the application are obtained by market purchase.
[0054] The following embodiments involve the following abbreviations, specifically referring to:
[0055] PCL: polycaprolactone;
[0056] COL I: type I collagen derived from bovine Achilles tendon;
[0057] rhCol III: recombinant human type III collagen;
[0058] HFIP: hexafluoroisopropanol;
[0059] HA: hyaluronic acid;
[0060] OHA: oxidized hyaluronic acid;
[0061] CMCS: carboxymethyl chitosan;
[0062] TGase: transglutaminase.
[0063] Embodiment 1
[0064] A preparation method of a multifunctional gradient structure artificial skin, and the specific steps are as follows:
[0065] 1) Preparation of the upper silica gel layer
[0066] 1mL of silica gel liquid A and 1mL of silica gel liquid B were stirred and mixed uniformly for 10 min, poured into a mold and leveled, and then left to stand at room temperature for 6h to obtain a silica gel film; wherein the components of the silica gel liquid A are silica, vinyl silicone oil, methyl silicone oil and platinum gold water, and the mass ratio of the silica, vinyl silicone oil, methyl silicone oil and platinum gold water is 0.35:0.47:0.178:0.002; the components of the silica gel liquid B are silica, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil, and the mass ratio of the silica, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil is 0.35:0.47:0.102:0.078.
[0067] 2) Preparation of intermediate layer P5C5 electrospun membrane
[0068] 0.75 g of PCL and 0.75 g of COL I were dissolved in 10 mL of HFIP, and stirred for 8 h to obtain a P5C5 solution with a concentration of 15 wt%, and the mass ratio of PCL to COL I was 5:5; 4 mL of the above P5C5 solution was taken, and electrospinning was performed using a 21G needle, with the flow rate of the spinning solution being 2 mL / h, the working voltage being 14 kV, the distance between the injector needle and the aluminum foil receiver being 15 cm, and the rotation speed of the aluminum foil receiver being 50 r / min; after electrospinning, a P5C5 electrospun membrane was obtained.
[0069] 3) Preparation of oxidized hyaluronic acid
[0070] 2 g of HA was dissolved in 200 mL of deionized water, 5 mmol (5 mL) of sodium periodate aqueous solution was slowly added to the above solution, and the solution was stirred at room temperature for 6 h in the dark, 1 mL of ethylene glycol was added and quenched at room temperature for 1 h, and then dialyzed in deionized water for 3 days, and then vacuum freeze-dried to obtain OHA.
[0071] 4) Preparation of lower layer OHA / CMCS / rhCol III hydrogel
[0072] TGase was dissolved in deionized water, and then OHA obtained in step 3) was added to obtain a mixed solution 1; CMCS and rhCol III were dissolved in deionized water to prepare a mixed solution 2; the mixed solution 1 and the mixed solution 2 were mixed uniformly under oscillation to obtain an OHA / CMCS / rhCol III hydrogel; wherein the mass-volume ratio of OHA to deionized water was 20 mg: 1 mL, the mass-volume ratio of CMCS to deionized water was 30 mg: 1 mL, the mass-volume ratio of rhCol III to deionized water was 20 mg: 1 mL, the mass-volume ratio of TGase to deionized water was 2.4 mg: 1 mL, and the total amount of water was 1 mL.
[0073] 5) Preparation of multifunctional gradient structure artificial skin
[0074] The silicone membrane prepared in step 1), the P5C5 electrospun membrane prepared in step 2), and the OHA / CMCS / rhCol III hydrogel prepared in step 4) were cut into the same size, and then stacked in the order of silicone membrane, P5C5 electrospun membrane, and OHA / CMCS / rhCol III hydrogel, and then combined in a vacuum environment for 72 h to obtain a multifunctional gradient structure artificial skin, wherein the thickness of the silicone membrane in the multifunctional gradient structure artificial skin was 0.5 mm, the thickness of the P5C5 electrospun membrane was 0.1-0.2 mm, and the thickness of the OHA / CMCS / rhCol III hydrogel was 4 mm.
[0075] Example 2
[0076] A preparation method of a multifunctional gradient structure artificial skin, the specific steps are:
[0077] 1) Preparation of intermediate layer P6C4 electrospun membrane
[0078] Dissolve 0.9g PCL and 0.6g COL I in 10mL HFIP, fully stir for 8h, obtain P6C4 solution with concentration of 15wt%, mass ratio of PCL and COL I is 6:4; take 4mL P6C4 solution, use 21G needle, set flow rate of spinning solution as 2mL / h, working voltage as 14kV, distance between injector needle and aluminum foil receiver as 15cm, rotation speed of aluminum foil receiver as 50r / min to perform electrospinning, after electrospinning, obtain P6C4 electrospun membrane.
[0079] 2) Preparation of silica gel-electrospun membrane
[0080] Stir 1mL silica gel solution A and 1mL silica gel solution B uniformly for 10min, pour into mold and flow flat, after standing reaction at room temperature for 6h, obtain silica gel membrane; cover P6C4 electrospun membrane prepared in step 1) on the above silica gel membrane, combine in vacuum environment for 72h, obtain silica gel-electrospun membrane; wherein, components of silica gel solution A are silica, vinyl silicone oil, methyl silicone oil and platinum gold water, mass ratio of silica, vinyl silicone oil, methyl silicone oil and platinum gold water is 0.35:0.47:0.178:0.002; components of silica gel solution B are silica, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil, mass ratio of silica, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil is 0.35:0.47:0.102:0.078.
[0081] 3) Preparation of oxidized hyaluronic acid
[0082] Take 2g HA and dissolve in 200mL deionized water, slowly add 5mmol (5mL) sodium periodate aqueous solution to the above solution, stir at room temperature for 6h in dark, add 1mL ethylene glycol and quench at room temperature for 1h, dialyze in deionized water for 3 days, vacuum freeze-dry to obtain OHA.
[0083] 4) Preparation of OHA / CMCS / rhCol Ⅲ hydrogel
[0084] The TGase is dissolved in deionized water, and then the OHA obtained in step 3) is added to obtain a mixed solution 1; the CMCS and rhCol III are dissolved in deionized water to prepare a mixed solution 2; the mixed solution 1 and the mixed solution 2 are mixed under oscillation to obtain the OHA / CMCS / rhCol III hydrogel; wherein the mass-volume ratio of OHA to deionized water is 20 mg: 1 mL, the mass-volume ratio of CMCS to deionized water is 30 mg: 1 mL, the mass-volume ratio of rhCol III to deionized water is 10 mg: 1 mL respectively, the mass-volume ratio of TGase to deionized water is 2.4 mg: 1 mL, and the total amount of water is 1 mL.
[0085] 5) Preparation of multifunctional gradient structure artificial skin
[0086] The silica gel-electrospun film obtained in step 2) is covered on the OHA / CMCS / rhCol III hydrogel obtained in step 4), and the multifunctional gradient structure artificial skin is obtained by combining under vacuum environment for 72 h, wherein the thickness of the silica gel film in the multifunctional gradient structure artificial skin is 0.5 mm, the thickness of the P6C4 electrospun film is 0.1-0.2 mm, and the thickness of the OHA / CMCS / rhCol III hydrogel is 4 mm.
[0087] Example 3
[0088] A preparation method of a multifunctional gradient structure artificial skin, and the specific steps are as follows:
[0089] 1) Preparation of intermediate layer P4C6 electrospun film
[0090] 0.6 g of PCL and 0.9 g of COL I are dissolved in 10 mL of HFIP, and stirred for 8 h to obtain a P4C6 solution with a concentration of 15 wt%, and the mass ratio of PCL to COL I is 4:6; 4 mL of the above P4C6 solution is taken, and electrospinning is performed by using a 21G needle, setting the flow rate of the spinning solution to 2 mL / h, the working voltage to 14 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, and the rotation speed of the aluminum foil receiver to 50 r / min; after electrospinning, a P4C6 electrospun film is obtained.
[0091] Steps 2) to 5) are the same as those in Example 2.
[0092] Example 4
[0093] A preparation method of a multifunctional gradient structure artificial skin, and the difference from Example 1 is that in step 4), the mass-volume ratio of rhCol III to deionized water is 10 mg: 1 mL respectively, and the others are the same as those in Example 1.
[0094] Example 5
[0095] A preparation method of a multifunctional gradient structure artificial skin, different from example 1 is that in step 4), the mass-volume ratio of rhCol III and deionized water is 30 mg: 1 mL respectively, and the others are the same as example 1.
[0096] Comparative example 1
[0097] A preparation method of a PCL electrospun film, the specific steps are: 1.5 g of PCL is dissolved in 10 mL of HFIP, and stirred for 8 h to obtain a PCL solution; 4 mL of the above PCL solution is taken, and electrospinning is carried out by using a 21G needle, setting the flow rate of the spinning solution to 2 mL / h, the working voltage to 14 kV, the distance between the syringe needle and the aluminum foil receiver to 15 cm, and the rotation speed of the aluminum foil receiver to 50 r / min; after electrospinning, a PCL electrospun film is obtained.
[0098] Comparative example 2
[0099] A preparation method of a multifunctional gradient structure artificial skin, different from example 1 is that in step 4), the mass-volume ratio of rhCol III and deionized water is 0 mg: 1 mL respectively, and the others are the same as example 1.
[0100] I. Observation of surface morphology of electrospun film
[0101] The micro-morphology of the electrospun films prepared in examples 1-3 and comparative example 1 was observed by SEM, and the results are shown in Figure 1 .
[0102] Figure 1 The micro-morphology (A), fiber diameter distribution (B), pore size distribution (D), fiber diameter statistical results (C) and pore size statistical results (E) of the electrospun films prepared in examples 1-3 and comparative example 1 are shown, wherein PCL is comparative example 1, P5C5 is example 1, P6C4 is example 2, and P4C6 is example 3 (the same below). From Figure 1As can be seen, the fibers of PCL, P6C4, P5C5 and P4C6 in the four electrospun membranes are smooth, dense and randomly oriented. The diameter of the fibers in the pure PCL electrospun membrane is 1.68±0.05 μm, while after the incorporation of COL I, the diameter of the fibers is significantly reduced, and there is no significant difference in the diameter of the fibers in the P6C4 electrospun membrane (0.67±0.03 μm), the P5C5 electrospun membrane (0.87±0.06 μm) and the P4C6 electrospun membrane (0.63±0.02 μm). Compared with PCL, the diameter of the fibers is significantly reduced, the electrospun membrane is more dense, the pore size is significantly reduced, and a more dense structure is formed. The pore size of the PCL electrospun membrane is 11.03±0.57 μm, and there is no significant difference in the pore size of the P6C4 electrospun membrane (3.93±0.17 μm), the P5C5 electrospun membrane (4.10±0.12 μm) and the P4C6 electrospun membrane (4.51±0.28 μm), which indicates that the electrospun membrane prepared in the application forms a dense barrier layer, which can effectively prevent bacteria from migrating to the inside of the material, and meets the basic requirements of the barrier membrane.
[0103] II. Hydrophilicity of the electrospun membrane
[0104] Figure 2 The water contact angle of the electrospun membrane prepared for Examples 1-3 and Comparative Example 1. From Figure 2 As can be seen, when the water droplets contact the surface of the material, the water contact angle of the PCL electrospun membrane prepared in Comparative Example 1 is 121.41±3.18°, the water contact angle of the P6C4 electrospun membrane prepared in Example 2 is 65.77±8.56°, the water contact angle of the P5C5 electrospun membrane prepared in Example 1 is 49.25±3.98°, and the water contact angle of the P4C6 electrospun membrane prepared in Example 3 is 41.75±3.52°. It can be seen that the more COL I content, the smaller the water contact angle of the electrospun membrane, and the better the hydrophilicity. This is because COL I contains a large number of hydrophilic groups such as amino, hydroxyl and carboxyl, which effectively improve the hydrophilicity of the material and can quickly absorb water droplets falling on the surface of the material. The good hydrophilicity of the electrospun membrane can promote cell adhesion and proliferation and effectively accelerate the wound repair process.
[0105] III. Mechanical properties of the electrospun membrane
[0106] Good mechanical properties can maintain the shape of the artificial skin during application. It is found by determining the tensile mechanical properties of each group of materials that the incorporation of an appropriate amount of COL I can improve the elastic modulus, tensile strength and ultimate load of the material.
[0107] Figure 3The mechanical properties of the electrospun films prepared in Examples 1-2 and Comparative Example 1 are shown, where A is the elastic modulus, B is the elongation at break, C is the tensile strength, and D is the ultimate load. Figure 3 As shown in Part A, the PCL / COL I electrospun film with an appropriate amount of COL I incorporated exhibits a higher elastic modulus than the PCL electrospun film. The elastic modulus of the PCL electrospun film is 2.44±0.16 MPa, the P6C4 electrospun film is 40.62±1.22 MPa, and the P5C5 electrospun film is 24.74±2.10 MPa. Figure 3 As shown in Part B, the elongation at break of the PCL electrospun film is 522.70±18.14%, the elongation at break of the P6C4 electrospun film is 58.89±1.32%, and the elongation at break of the P5C5 electrospun film is 50.07±2.55%. Figure 3 As can be seen from section C, the tensile strength of the PCL electrospun film is 2.96±0.05MPa, the tensile strength of the P6C4 electrospun film is 6.71±0.19MPa, and the tensile strength of the P5C5 electrospun film is 2.19±0.12MPa. (From...) Figure 3 As shown in section D, the ultimate load of the PCL electrospun film is 6.04±0.10N, the ultimate load of the P6C4 electrospun film is 13.31±0.20N, and the ultimate load of the P5C5 electrospun film is 3.12±0.01N. In summary, it can be seen that the electrospun film prepared by incorporating an appropriate amount of COLⅠ has superior mechanical properties.
[0108] IV. Mechanical Properties of Silicone-Electrospun Film
[0109] Figure 4 The mechanical properties of the silicone film and silicone-electrospun film prepared in step 2) of Example 2 are shown, where A is the elastic modulus, B is the elongation at break, C is the tensile strength, D is the ultimate load, Silica gel is the silicone film, and Bilayer is the silicone-electrospun film. Figure 4 It can be seen that, compared with silicone film, the elastic modulus of silicone-electrospun film is higher (see...). Figure 4 Part A of the text), tensile strength (see ... Figure 4 Part C in the middle) and ultimate load ( Figure 4 The D portion of the membrane was significantly improved, indicating that the composite of silicone membrane and electrospun membrane has superior mechanical properties.
[0110] V. Observation of hydrogel surface morphology
[0111] The surface morphology and structure of the hydrogels prepared in Examples 1, 4-5, and Comparative Example 2 were observed by SEM. The results are shown in the figure. Figure 5 .
[0112] Figure 5 Micro-morphology (A), pore size distribution (B) and pore size statistics (C) of the hydrogels prepared for Example 1, Example 4-5 and Comparative Example 2, wherein R0 is Comparative Example 2, R1 is Example 4, R2 is Example 1, and R3 is Example 5. From A part of Figure 5 , it can be seen that R0, R1, R2 and R3 all exhibit a porous, interconnected three-dimensional network structure, which is conducive to cell migration and material metabolism. By counting the pore size of the hydrogel, it can be seen that the pore size of R0 is 374.82±6.16 μm, the pore size of R1 is 300.38±5.43 μm, the pore size of R2 is 311.96±8.58 μm, and the pore size of R3 is 262.89±5.03 μm. It can be observed that the pore size is reduced to a certain extent with the incorporation of rhCol Ⅲ. The porous structure of the hydrogel is conducive to the migration of fibroblasts and promotes wound repair.
[0113] VI. Biocompatibility of artificial skin
[0114] By exploring the effect of material extract on cell proliferation, the influence of the material on the activity of the surrounding tissue in the body is simulated. According to the ISO 10993-12 standard, the sterilized silicone or the freeze-dried hydrogel of each group is soaked in fresh culture medium at a standard of 0.1 g / mL at 37°C for 24 h. After centrifugation, the supernatant is aspirated, and the silicone extract or hydrogel extract is obtained by passing through a 0.22 μm filter membrane to fully sterilize; the sterilized electrospun film is soaked in fresh culture medium at a standard of 6 cm 2 / mL at 37°C for 24 h, and then the supernatant is aspirated. The electrospun film extract is obtained by passing through a 0.22 μm filter membrane to fully sterilize. L929 cells are inoculated in a 96-well plate at a density of 3000 cells / well. After 24 h of culture, the culture medium of the experimental group is replaced with the silicone extract, the electrospun film extract or the hydrogel extract, and the blank control group is the 1640 culture medium. The absorbance of each group is detected by CCK-8 experiment at 1, 2 and 3 days, and the biocompatibility of each group is analyzed. The results are shown in Figure 6 .
[0115] Figure 6 Cytotoxicity results of the silicone film prepared for Example 1 (A), the electrospun film prepared for Example 1-3 and Comparative Example 1 (B), and the hydrogel prepared for Example 1, Example 4-5 and Comparative Example 2 (C). From A part of Figure 6 , it can be seen that the silicone group significantly promotes the proliferation of L929 cells at 2 days of culture; from B part of Figure 6 , it can be seen that at 1, 2 and 3 days, the absorbance of the electrospun film has no significant difference with that of the control group; from C part of Figure 6As can be seen from part C in the figure, the R2 group can significantly promote the proliferation of L929 cells on the 2nd and 3rd days of culture, indicating that the addition of rhCol III increases the biocompatibility of the hydrogel. In summary, the three layers of the artificial skin can maintain the viability of the cells, indicating that the material has good biocompatibility and no cytotoxicity.
[0116] Seven, the cell migration promoting ability of the hydrogel layer
[0117] In the process of injury repair, endogenous fibroblasts can migrate to the injured site, which is crucial for tissue regeneration. By exploring the effect of different concentrations of rhCol III on the horizontal migration of cells, the influence of the material on the surrounding cells in vivo is simulated. According to the ISO 10993-12 standard, the sterilized freeze-dried R0 hydrogel (Comparative Example 2) is soaked in fresh culture medium at a standard of 0.1 g / mL, 37°C for 24 h, then centrifuged to remove the supernatant, and the 0.22 μm filter membrane is used to fully sterilize the serum-free R0 hydrogel extract; rhCol III is dissolved in fresh culture medium at a standard of 10 mg / mL, 20 mg / mL, and 30 mg / mL, and the supernatant is removed, and the 0.22 μm filter membrane is used to fully sterilize the serum-free culture medium containing different concentrations of rhCol III. L929 cells are inoculated in a six-well plate at a density of 30×10 4 cells / well, and cultured until the cell density is 100%. A 200 μL gun head is used to evenly draw lines in the middle of each well, and the floating cells are washed clean with PBS. Serum-free 1640 culture medium (blank control group), serum-free hydrogel extract, or different concentrations of rhCol III serum-free culture medium are added for culture. At 0 h, 12 h, and 24 h, the cell migration is recorded by optical microscopy, and the results are shown in Figure 7 .
[0118] Figure 7 The effects of the control group, the hydrogel prepared in Comparative Example 2, and different concentrations of rhCol III on cell migration and cell migration rate statistics are shown in the table. Control is the control group, R0 is Comparative Example 2, 10 mg / mL, 20 mg / mL, and 30 mg / mL are the concentrations of rhCol III, A is the effect of the control group and different concentrations of rhCol III on cell migration, B is the cell migration rate statistics of the control group and different concentrations of rhCol III, C is the effect of the control group and the hydrogel prepared in Comparative Example 2 on cell migration, and D is the cell migration rate statistics of the control group and the hydrogel prepared in Comparative Example 2. From Figure 7As shown in part A and part B of FIG. 12, the cell migration rate of the control group was 20.75±2.79% after 12h, and 43.45±5.16% after 24h. The group containing human recombinant collagen type III can promote cell migration, and the group with a concentration of 10mg / mL has the most significant promotion effect, with a cell migration rate of 39.72±1.52% after 12h, and a cell migration rate of 65.65±3.03% after 24h, and the wound surface is close to closure, indicating that the hydrogel group containing human recombinant collagen type III can promote cell migration. Figure 7 As shown in part C and part D of FIG. 13, the cell migration rate of the control group was 18.44±2.26% after 12h, and the cell migration rate of the R0 group was 21.69±3.32%. The cell migration rate of the control group was 31.70±3.32% after 24h, and the cell migration rate of the R0 group was 37.87±2.35%, indicating that the hydrogel without rhCol III has no significant effect on cell migration.
[0119] The above is only a preferred specific embodiment of the present application, but the protection scope of the present application is not limited thereto, and any person skilled in the art can easily think of changes or replacements within the technical range disclosed by the present application, which should be covered within the protection scope of the present application.
Claims
1. A multi-functional gradient structure artificial skin, characterized by, The multi-functional gradient structure artificial skin comprises an upper layer, a middle layer and a lower layer which are adhered to each other; the upper layer is a silica gel layer, the middle layer is a degradable high polymer / natural bioactive protein composite layer, and the lower layer is a hydrogel layer; the raw materials for preparing the hydrogel layer comprise oxidized hyaluronic acid, carboxymethyl chitosan and collagen.
2. The multifunctional gradient structure artificial skin according to claim 1, characterized by, The raw materials for preparing the silica gel layer comprise silica gel liquid A and silica gel liquid B; the components of the silica gel liquid A comprise silicon dioxide, vinyl silicone oil, methyl silicone oil and platinum gold water; the components of the silica gel liquid B comprise silicon dioxide, vinyl silicone oil, methyl silicone oil and hydrogen-containing silicone oil; the mass ratio of the silica gel liquid A to the silica gel liquid B is (0.5-2):
1.
3. The multi-functional gradient structure artificial skin according to claim 1, wherein The degradable high polymer in the degradable high polymer / natural bioactive protein composite layer is selected from polycaprolactone, and the natural bioactive protein is selected from type I collagen.
4. The multi-functional gradient structure artificial skin according to claim 1, wherein The mass ratio of the degradable high polymer to the natural bioactive protein in the degradable high polymer / natural bioactive protein composite layer is (4-6):(6-4).
5. The multi-functional gradient structure artificial skin according to claim 1, wherein The preparation method of the degradable high polymer / natural bioactive protein composite layer comprises: taking the degradable high polymer and the natural bioactive protein as raw materials, taking hexafluoroisopropanol as a solvent, and preparing the degradable high polymer / natural bioactive protein composite layer through electrospinning.
6. The multifunctional gradient structure artificial skin according to claim 5, characterized in that, The process parameters of the electrospinning comprise: a spinning liquid flow rate of 1-2 mL / h, a working voltage of 13-15 kV, an aluminum foil receiver rotating speed of 45-50 r / min, a distance between a syringe needle and the aluminum foil receiver of 15-17 cm, and a needle specification of 21G.
7. The multifunctional gradient structure artificial skin according to claim 1, characterized by, The mass ratio of the oxidized hyaluronic acid, the carboxymethyl chitosan and the collagen is 20:30:(10-30).
8. The multi-functional gradient structure artificial skin according to claim 1, wherein, The raw materials for preparing the hydrogel layer further comprise glutamine transaminase; the mass ratio of the glutamine transaminase to the oxidized hyaluronic acid is 2.4:
20.
9. A method for producing the multi-functional gradient structure artificial skin according to any one of claims 1 to 8, characterized by, The method comprises the following steps: The silica gel layer, the degradable high polymer / natural bioactive protein composite layer and the hydrogel layer are prepared respectively; then the silica gel layer, the degradable high polymer / natural bioactive protein composite layer and the hydrogel layer are combined through vacuum compounding to obtain the multi-functional gradient structure artificial skin; the time for the vacuum compounding is 24-72 h.
10. Use of the multi-functional gradient structure artificial skin according to any one of claims 1-8 in the preparation of a chronic wound repair material.
Citation Information
Patent Citations
Functionalized derivatives of hyaluronic acid and formation of hydrogels in situ using same
CA2344215A1
Polycaprolactone / collagen / quaternary ammonium salt electrospun composite fiber membrane and method for preparing same
CN107519524A
Artificial skin and preparation method thereof
CN109602958A
Enzyme-loaded bacterial cellulose-based composite antibacterial hydrogel dressing and preparation method thereof
CN110507848A
Preparation method and applications of chitosan polypeptide derivative self-cross-linking hydrogel taking oxidized hyaluronic acid as cross-linking agent
CN111019162A